Empower the private sector to invest in Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Lucy Muchoki, CEO, Pan African Agribusiness & Agro-Industry Consortium talks about empowering the private sector to investment in Agriculture. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/